The Pharmacogenomics Aspects of Drugs Used in COVID-19 Treatment - Khan, Gazala Afreen; Elsayed, Yomna Rabba; Said, Marwa Osama (Journal of Medicine, 2022)
The increase in mortality and morbidity related to the novel COVID-19 virus led researchers to work ondeveloping new therapies to destroy the virus. Numerous clinical trials have started to find drugs that willeffectively treat the signs and symptoms of the virus. This review aims to summarize the pharmacogenomicaspects of drugs such as hydroxychloroquine, chloroquine, azithromycin, remdesivir, favipiravir, ribavirin,lopinavir/ritonavir, darunavir/cobicistat, interferon beta-1b, tocilizumab, ruxolitinib, baricitinib, andcorticosteroids used in the treatment of this virus. The data will be collected from various websites such asPubMed, Lancet, WHO website, PharmGKB website, IDSA Guidelines on the treatment & management ofCOVID-19 Patients, the U.S. Food and Drug Administration (FDA) product labeling, and pharmacogenomicstables. Incomplete data exists related to the efficacy and safety of these drugs and healthcare providers arestruggling to make the right treatment choices. Drug-gene variants may alter the pharmacokinetics andsafety of some drugs and thus produce adverse drug reactions. Therefore, pharmacogenomics may helpdoctors decide the correct course of treatment by knowing the genetic makeup of an individual. This caneventually help to eliminate adverse drug reactions and reduce the mortality rate. J MEDICINE 2022; 23: 61-76